Adaptation of a standard extended-release naltrexone (XR-NTX) protocol for rural re-entering offenders with OUD - Michele Staton; Hannah K. Knudsen; Sharon L. Walsh; Carrie Oser; Erika Pike; Michelle Lofwall (BMC, 2021)
Abstract Background Despite a growing body of empirical support for the effectiveness of extended-release naltrexone (XR-NTX) to reduce opioid relapse among people with opioid use disorder (OUD) transitioning from a correctional facility to the community, continuity of care following release remains challenging. This paper describes a research-based adaptation of a state's standard of care XR-NTX protocol using the ADAPT-ITT framework for delivery in a non-traditional, non-treatment, community criminal justice setting (P&P office), as well as the expansion of services by a local Federally Qualified Health Center (FQHC) provider who would, for the first time, be going to the jail and P&P office to provide XR-NTX and related treatment. Method The present study focuses on the first seven phases (Assessment through Training) of the ADAPT-ITT framework in the adaptation of the Department of Corrections (DOC) protocol in preparation for a pilot trial for induction in a rural jail and during the transition to a rural community. Expert clinical review and focus groups with key stakeholders in criminal justice supervision and the local providers in the FQHC informed the needed adaptations to the existing XR-NTX protocol for initiation at the jail and ongoing administrations in the community. Results Findings from stakeholder focus groups, study team review, topical expert review, and a theater test suggested that there were critical adaptations needed in both content and context at the patient and clinic level. Conclusion Health and justice officials should consider the need to tailor and adapt evidence-based approaches for real-world locations that high-risk, justice-involved individuals visit in order to reduce barriers and increase access to critically needed treatment for OUD.